FPGA based control circuit for single phase inverter - Muhammad Imran, Ahmad; Zulkifli, Husin; Hasliza, A. Rahim; Ismail, B.; Mohamad Suhaizal, Abu Hassan; Mohd Nazrin, Md Isa (ACTA Press, 2009)
Link to publisher's homepage at http://www.actapress.com